2012
DOI: 10.1038/jid.2012.196
|View full text |Cite
|
Sign up to set email alerts
|

CD133 Is a Marker for Long-Term Repopulating Murine Epidermal Stem Cells

Abstract: Maintenance, repair and renewal of the epidermis are thought to depend on a pool of dedicated epidermal stem cells. Like for many somatic tissues, isolation of a nearly pure population of stem cells is a primary goal in cutaneous biology. We used a quantitative transplantation assay, using injection of keratinocytes into subcutis combined with limiting dilution analysis, to assess the long-term repopulating ability of putative murine epidermal stem populations. Putative epidermal stem cell populations were iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
1
15
3
Order By: Relevance
“…In this mouse model, progenitor CD133 cells were lacZ positive whereas the CD133 progeny were GFP positive. LacZ and GFP positive cells were observed only in the hair follicles of intact mouse skins (Figure 6b) as reported by others (Charruyer et al , 2012). …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In this mouse model, progenitor CD133 cells were lacZ positive whereas the CD133 progeny were GFP positive. LacZ and GFP positive cells were observed only in the hair follicles of intact mouse skins (Figure 6b) as reported by others (Charruyer et al , 2012). …”
Section: Resultssupporting
confidence: 87%
“…Lineage analysis has also demonstrated that follicles can arise from cells outside of the hair follicle stem cell niche, suggesting that cells found in the epidermis can assume a hair follicle stem cell phenotype (Ito et al , 2007). A recent study reported that CD133 is a marker for long-term repopulating murine epidermal stem cells and CD133+ keratinocytes formed both hair follicles and epidermis after injection into immunodeficient mice (Charruyer et al , 2012). Our lineage tracing studies demonstrated the presence of CD133+ cells in the hair follicles of intact skin (Figure 6b).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports showing that normal stem cells and induced pluripotent stem cells retain young mitochondria with high metabolic capacity [54, 110, 111]. Similarly, physiological aging may occur in cancer where CSCs show hyperpolarized Δψ m [24, 44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the Ghadially group (Charruyer et al, 2012) achieved a 5.2-fold enrichment with CD133 þ DCm hi keratinocytes over the a6 þ CD34 þ controls. Moreover, this enriched subpopulation displayed superior long-term repopulating and self-renewal abilities; it was composed of label-retaining cells, but retained the ability to reconstitute an epithelium with the epidermis, hair follicles, and sebaceous glands.…”
mentioning
confidence: 94%
“…Furthermore, keratinocyte stem cells have long been implicated as target cells for non-melanoma skin cancer (Owens and Watt, 2003), and the identification of CD133 in a subset of normal hair follicle bulge stem cells, as shown by Ghadially and co-workers (Charruyer et al, 2012), may have important implications for skin tumorigenesis. Although CD133 is a transmembrane protein of unknown function, as neither ligands nor signaling pathways have been found to associate with it, multiple lines of evidence indicate that the presence of CD133 on the cell surface may serve as a functionally relevant biomarker for carcinogenesis.…”
mentioning
confidence: 96%